Data mining to map the nutrition value of industrial cheese produced in France - Nguyen, Dinh T; Singh, Swati; Goel, Saurav (Biomaterials and Polymers Horizon, 2022)
Cheese is a dairy product with a long history in the human diet. In countries such as France, cheese is one of the strongest attractions for visitors from around the globe. The cheese was thought of as only a source of energy alone; however, with advances in nutritional science, cheese has become a rich source of essential nutrients such as proteins, bioactive peptides, amino acids, vitamins and minerals. This perspective offers new insights into the nutrition analysis of various types of cheese sold in France, using advanced data visualization and analysis techniques. This article aims to raise awareness about making an informed selection of the type of cheese people should consume as a long-term measure of taking a health-conscious diet. Overall, the study provides a testbed for turophiles (cheese lovers) in selecting the right kind of cheese to relish themselves while taking care of their health condition depending on their physical condition, particularly lactose intolerance.